Studi Kualitas Bahan Bakar Cair Hasil Pirolisis Limbah Plastik dengan Penambahan Aditif Solketal: indonesia - Fitri, Noor; Royhan, Hafizh; Maulidia, Nabila Ayu; Arman, Reydi; Irawan, Ari Irawan; Supriadi, Eko; Jahiding, Muhammad Jahiding; Mashuni (Asian Journal of Innovation and Entrepreneurship, 2026)
The increasing volume of global plastic waste, which has exceeded 367 million tons per year, has created a serious environmental problem, particularly in Indonesia, which contributes about 17% of the national waste. Mechanical recycling and direct incineration are considered less optimal due to limited product quality and potential pollution. As an alternative, pyrolysis offers a promising technology to convert plastic waste into liquid fuel (pyrolysis oil) with characteristics similar to conventional fuels. This study utilized even-numbered plastic wastes (HDPE, LDPE, PS) through pyrolysis at 300 °C for 45 minutes with a reactor capacity of 5 kg, producing 1 L of pyrolysis oil per batch. Characterization results indicated that most fuel parameters met ASTM standards, such as Total Acid Number (0.02 mg KOH/g), flash point (61 °C), and sulphur content (0.005%), although some deviations were found in water content, carbon residue, and cetane number. To improve its quality, 0.2% solketal was added as an oxygenated additive, which significantly enhanced engine performance and reduced emissions. Performance testing using a D-4D diesel engine demonstrated improved fuel efficiency, while emission tests showed lower opacity and CO levels, along with more complete combustion indicated by higher CO₂ emissions. These findings confirm that integrating pyrolysis with solketal additives can produce a more efficient, environmentally friendly alternative fuel with potential for application in sustainable energy industries.